HMG-CoA Reductase Inhibitors Relieve Endoplasmic Reticulum Stress by Autophagy Inhibition in Rats With Permanent Brain Ischemia - Zhang, Tao; Lu, Dan; Yang, Wanyong; Shi, Changzheng; Zang, Jiankun; Shen, Lingling; Mai, Hongcheng; Xu, Anding (Frontiers in Neuroscience, 2018)
Exploring and expanding the indications of common clinical drugs, such as statins, is important to improve the prognosis of patients with permanent cerebral infarction. It has been suggested that reversing the defects in cellular autophagy and ER stress with statin therapy may be a potential treatment option for reducing ischemic damage. Male Sprague-Dawley rats underwent permanent middle cerebral artery occlusion (PMCAO) by electrocoagulation surgery. Atorvastatin (ATV, 10 mg/kg/day) or vehicle was administered intraperitoneally. Rats were divided into the vehicle-treated (SHAM), ATV pretreatment for MCAO (AMCAO), and 3-methyladenine (3MA) combined with ATV pretreatment (3MAMCAO) groups. Magnetic resonance imaging, as well as immunohistochemical and Western blot assessments, were performed 24 h after MCAO. Each ATV-treated group demonstrated significant reductions in infarct volume compared with that in the vehicle-treated group at 24 h after MCAO, which was associated with autophagy reduction and ER stress attenuation in neurons and neovascularization. Next, Western blotting was used to detect the levels of the autophagy-related proteins LC3B and P62 and of ER stress pathway proteins. However, 3MA significantly partially inhibited the ER stress pathway via limiting the autophagic flux in the AMCAO group. In conclusion, our results imply that the neuroprotective function of ATV depends on autophagic activity to diminish ER stress-related cell apoptosis in rats with PMCAO and suggest that compounds that inhibit autophagic activity might reduce the neuroprotective effect of ATV after brain ischemia.